Faktor-Faktor yang Mempengaruhi Kinerja Awak Kapal pada PT. Pelni (Persero) di Pelabuhan Tanjung Wangi - Wage Mulyono; Hary Sulaksono; Dedy Wijaya Kusuma (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
The Influence of Crew Skills, Safety Equipment Maintenance, Safety Regulation Compliance, and Crew Work Coordination on Crew Performance at PT. Pelni (PERSERO) in Tanjung Wangi Port. This study aims to analyze the influence of crew skills, safety equipment maintenance, compliance with safety regulations, and work coordination on crew performance at PT Pelni (Persero) in Tanjung Wangi Port. This study uses a quantitative approach with a survey method through questionnaires and multiple linear regression analysis. The results of the study indicate that partially, crew skills (X1), safety regulation compliance (X3), and crew work coordination (X4) do not have a significant effect on crew performance (Y). However, safety equipment maintenance (X2) is proven to have a significant effect partially on crew performance (Y). Meanwhile, simultaneous analysis reveals that the four variables, namely crew skills (X1), safety equipment maintenance (X2), safety regulation compliance (X3), and crew work coordination (X4), together have a significant impact on improving crew performance (Y). These findings indicate that although some factors are not significant individually, the combination of the four variables makes a significant contribution in determining the overall level of crew performance.